Experimental Comparison of the Effect of Microtalc and Nanoclay on the Structural Properties of Polyethylene Foams Fabricated by Rotational Molding - Taher Azdast; Saeed Karimzadeh; Rezgar Hasanzadeh; milad moradian; Ali Doniavi; Hamidreza Akrami (علوم و تکنولوژی پلیمر, 2022)
Hypothesis: Polymeric foams have fascinating specific properties due to their cellular and porous structure and these properties have attracted much attention in industrial and scientific societies nowadays. The variations in cellular structure of polymeric foams including expansion ratio, cell density, and cell size may affect their final properties. For this reason, it seems necessary to study the effect of process parameters on the cellular structure of polymeric foams. On the other hand, the rotational molding method is developing rapidly compared to other processing methods due to its ability to fabricate large complex hollow parts Different process parameters can affect the structural properties of polymeric foams Utilizing nucleation agents as a material parameter improves the structural properties of polymeric foams significantly in different processing methods.Methods: The effect of adding two types of nucleating agents including talc microparticles and clay nanoparticles in different sizes on the structural properties of polyethylene foams made by rotational molding process was investigated Azodicarbonamide was used as the chemical blowing agent. Talc microparticles (1% by weight) and clay nanoparticles were added to polyethylene and foamed using rotational molding process. Cell density, cell size, and expansion ratio were investigated as structural properties.Findings: The findings revealed that the effect of talc microparticles on increasing cell density and decreasing cell size was more significant than the effect of clay nanoparticles. Cell density of polyethylene foam was improved by 96% and 89% by adding 1% (by weight) of talc microparticles and clay nanoparticles, respectively. A 20% and 17.5% decrease in the cell size of polyethylene foam was also observed with the addition of 1% (by weight) of talc microparticles and clay nanoparticles respectively.